2000
DOI: 10.1097/00000539-200008000-00029
|View full text |Cite
|
Sign up to set email alerts
|

Small-Dose Clonidine Prolongs Postoperative Analgesia After Sciatic-Femoral Nerve Block with 0.75% Ropivacaine for Foot Surgery

Abstract: This prospective, randomized, double-blinded study demonstrated that, when providing combined sciatic-femoral nerve block for hallux valgus repair, the addition of 1 microg/kg clonidine to 0.75% ropivacaine prolongs the duration of postoperative analgesia by 3 h, with only a slight and short-lived increase in the degree of sedation and no hemodynamic adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
35
1
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 17 publications
10
35
1
5
Order By: Relevance
“…The large diameter of the sciatic nerve may lead to a less foreseeable blockade onset time, as compared to other peripheral blocks, although this pharmacological effect is primarily influenced by chemical properties of the anesthetic drug. In our investigation, mean onset time was 6 minutes, relatively lower than previous studies using other anesthetics by different routes, such as ropivacaine (10 to 25 minutes) 13,14,[24][25][26] and bupivacaine (20 to 30 minutes) 27 . It has to be stressed that no patient needed analgesic complementation during surgery, differently from what has been reported by other authors 14 .…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…The large diameter of the sciatic nerve may lead to a less foreseeable blockade onset time, as compared to other peripheral blocks, although this pharmacological effect is primarily influenced by chemical properties of the anesthetic drug. In our investigation, mean onset time was 6 minutes, relatively lower than previous studies using other anesthetics by different routes, such as ropivacaine (10 to 25 minutes) 13,14,[24][25][26] and bupivacaine (20 to 30 minutes) 27 . It has to be stressed that no patient needed analgesic complementation during surgery, differently from what has been reported by other authors 14 .…”
Section: Discussioncontrasting
confidence: 66%
“…Nesta investigação, observou-se latência média de 6 minutos, relativamente menor que estudos prévios que utilizaram outros anestésicos por diferente vias, como a ropivacaí-na, cuja latência média foi de 10 a 25 minutos 13,14,[24][25][26] , e bupivacaína de 20 a 30 minutos 27 . Ressalta-se a observação que nenhum paciente necessitou complementação analgésica durante a cirurgia, diferentemente referido por outros autores 14 .…”
Section: Resultsunclassified
“…The first one is epinephrine, which prolongs the duration of block for local anesthetics of intermediate duration of action (mepivacaine, lidocaine), and which also serves as a marker for intravascular injection. The second useful adjuvant is clonidine which also prolongs the duration of most types of peripheral nerve block [37][38][39][40][41][42][43] The presence and clinical significance of peripheral opioid receptors that may be migratory and activated by inflammatory states, is widely debated. Candido et al [44,45] showed that buprenorphine added to a local anesthetic mixture (mepivacaine 1%, tetracaine 0.2% and epinephrine 1:200,000) significantly prolonged analgesia in both axillary and subclavian perivascular brachial plexus blocks, by up to 30 hours.…”
Section: Local Anesthetics and Additivesmentioning
confidence: 99%
“…12,18,24 Low dose clonidine is also reported to prolong postoperative analgesia with no clinically relevant side effects. 9 Clonidine may act as a central or peripheral sympatholytic agent, resolving sympathetically mediated pain. 25 In lower doses as used here, the sedative and hypotensive effects of clonidine are attenuated and act to offset the stimulating effects of ketamine.…”
Section: Statisticsmentioning
confidence: 99%
“…Several drugs, including clonidine, ketamine, magnesium, lidocaine, ketorolac, and steroids have all been shown to be analgesic. [6][7][8][9][10][11] Combining these drugs may potentiate analgesia by separate actions and decrease the risk of side effects by lowering the effective dose for each agent. 12,13 The purpose of this study was to compare fentanyl analgesia with a combination of non-opioid drugs for gastric bypass surgery.…”
mentioning
confidence: 99%